Kajian Peran Naratif dan Simbolis Desain Produk dalam Cerita Rakyat Indonesia - Nandang Septian; Rafeah Legino; Yulyta Kodrat Prasetyaningsih (UNIVERSITAS INDO GLOBAL MANDIRI, 2026)
Indonesian folklore does not convey moral and social values only but also depicts the involvement of various physical objects or products that serve both narrative and symbolic functions. This phenomenon raises a fundamental question; why do certain products or objects appear in folklore, and how can their meanings be interpreted within the context of product design. This article aims to unfolding the role of objects or artefacts in Indonesian folklore and their cultural significance, both in the traditional context and its application in the modern era. This study uses Qualitative Content Analysis combined with Comparative Narrative approach to examine the role and meaning of product design objects in 38 purposively selected folklores that represent Indonesia's cultural and geographic diversity. The study identifies the roles of designed objects or products, such as weapons, textiles, musical instruments, jewellery, vehicle, and tools. Each object serves specific narrative functions, including magical aid, moral testing, and conflict resolution, while simultaneously reflecting the material culture and belief systems of the communities that produced them. Furthermore, the findings emphasise the potential of folklore as a resource for contemporary product design, inspiring culturally grounded yet innovative creations. The study concludes that understanding the narrative and symbolic roles of objects in folklore can bridge traditional cultural heritage and modern design practices, fostering both cultural sustainability and creative innovation.